Enhancing Students’ Interest in Arabic Learning through H5P-Based Interactive E-Books - Wildan Afkar; Ahmad Farhan Rif'an Najib; Ahmad Inzimam Haq (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2026)
The growing integration of digital technology in Islamic boarding school environments has created increasing demand for interactive learning media that can sustain students' affective engagement in Arabic language instruction. This study examines the effectiveness of Lumi Education (H5P)-based interactive e-books in enhancing junior high school students' interest in learning Arabic vocabulary, employing a quasi-experimental pretest-posttest control group design with 60 students from grades VIII–IX divided equally into experimental and control groups. Learning interest is measured through five indicators, namely pleasure, attention, interest, active involvement, and desire to learn independently. The measurement was carried out using a 25-point Likert scale questionnaire that has been tested for validity and reliability. Educators and curriculum developers working in digitally transitioning Islamic educational settings may find interactive e-books a viable instructional medium for fostering affective engagement, particularly in contexts where learner homogeneity and structured intervention conditions are present. Broader adoption should, however, account for instrument sensitivity and participant diversity to ensure that reported effects are appropriately calibrated to varied educational environments.